2019
DOI: 10.1101/gad.329771.119
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma plasticity and phenotypic diversity: therapeutic barriers and opportunities

Abstract: An incomplete view of the mechanisms that drive metastasis, the primary cause of cancer-related death, has been a major barrier to development of effective therapeutics and prognostic diagnostics. Increasing evidence indicates that the interplay between microenvironment, genetic lesions, and cellular plasticity drives the metastatic cascade and resistance to therapies. Here, using melanoma as a model, we outline the diversity and trajectories of cell states during metastatic dissemination and therapy exposure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
281
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(317 citation statements)
references
References 229 publications
(321 reference statements)
16
281
0
3
Order By: Relevance
“…The plasticity of melanoma as enabler of drug resistance was a subject of most recent reviews [16,37,53]. Arozarena and Wellbrock [53] proposed three phases of response to MAPK inhibitor therapy in MITF high melanomas, initial with induced reprogramming, adaptive with enhanced drug tolerance and acquired with drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasticity of melanoma as enabler of drug resistance was a subject of most recent reviews [16,37,53]. Arozarena and Wellbrock [53] proposed three phases of response to MAPK inhibitor therapy in MITF high melanomas, initial with induced reprogramming, adaptive with enhanced drug tolerance and acquired with drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to expression of AXL, NGFR and a lineage-specific transcription factor MITF, expression of SOX transcription factors that are associated with control of cancer cell plasticity, is broadly used to classify the phenotypes of melanoma cells [36,37]. First, the expression of SOX2, SOX9, and SOX10 at the transcript levels was compared between drug-naïve cell lines.…”
Section: Genes From the Sex-determining Region Y-box (Sox) Family Arementioning
confidence: 99%
“…This gene regulates the expression of pigmentation related molecules, which are recognized by T-cells, thus contributing to the highly immunogenic nature of melanoma [5]. Several studies have shown that the MITF low cells are dedifferentiated, invasive, and apoptosis-resistant [6][7][8], which gives them the ability to survive harsh conditions, such as under targeted and/or immunotherapy agents [5]. Given the fact that melanomas, under harsh conditions, can become enriched in MITF low cells and that these are more capable of escaping T-cell recognition, loss of MITF may be a mechanism for tumor cells to evade the immune system [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various different studies, including gene expression studies of tumours, immunohistochemical analysis of melanoma samples and singlecell sequencing studies of patient-derived xenografts suggest the existence of different cell types in melanoma tumours. This cellular heterogeneity is believed to reflect the associated ability of tumour cells to switch their phenotype from proliferative, non-invasive cells to quiescent, invasive cells and back, thus allowing metastasis and the escape from therapeutic intervention (reviewed in [8]. This has been summarized in the phenotype switching model which suggests that melanoma cells can switch between invasive and proliferative states allowing them to either grow and form tumours or metastasize to a new site [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This cellular heterogeneity is believed to reflect the associated ability of tumour cells to switch their phenotype from proliferative, non-invasive cells to quiescent, invasive cells and back, thus allowing metastasis and the escape from therapeutic intervention (reviewed in [8]. This has been summarized in the phenotype switching model which suggests that melanoma cells can switch between invasive and proliferative states allowing them to either grow and form tumours or metastasize to a new site [8,9]. Understanding the molecular mechanisms underlying the phenotypic plasticity of melanoma cells is key to addressing the metastatic potential of melanoma cells.…”
Section: Introductionmentioning
confidence: 99%